In Utero Exposure to Environmental Tobacco Smoke Increases Neuroinflammation in Offspring - Durão, Ana Carolina Cardoso dos Santos; Brandão, Wesley Nogueira; Bruno, Vitor; W. Spelta, Lídia Emmanuela; Duro, Stephanie de Oliveira; Barreto dos Santos, Nilton; Paranhos, Beatriz Aparecida Passos Bismara; Zanluqui, Nágela Ghabdan; Yonamine, Maurício; Pierre Schatzmann Peron, Jean; Munhoz, Carolina Demarchi; Marcourakis, Tania (Frontiers in Toxicology, 2022)
The embryonic stage is the most vulnerable period for congenital abnormalities. Due to its prolonged developmental course, the central nervous system (CNS) is susceptible to numerous genetic, epigenetic, and environmental influences. During embryo implantation, the CNS is more vulnerable to external influences such as environmental tobacco smoke (ETS), increasing the risk for delayed fetal growth, sudden infant death syndrome, and immune system abnormalities. This study aimed to evaluate the effects of in utero exposure to ETS on neuroinflammation in the offspring of pregnant mice challenged or not with lipopolysaccharide (LPS). After the confirmation of mating by the presence of the vaginal plug until offspring birth, pregnant C57BL/6 mice were exposed to either 3R4F cigarettes smoke (Kentucky University) or synthetic air. Enhanced glial cell and mixed cell cultures were prepared from 3-day-old mouse pups. After cell maturation, both cells were stimulated with LPS or saline. To inhibit microglial activation, minocycline was added to the mixed cell culture media 24 h before LPS challenge. To verify the influence of in utero exposure to ETS on the development of neuroinflammatory events in adulthood, a different set of 8-week-old animals was submitted to the Autoimmune Experimental Encephalomyelitis (EAE) model. The results indicate that cells from LPS-challenged pups exposed to ETS in utero presented high levels of proinflammatory cytokines such as interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNFα) and decreased cell viability. Such a proinflammatory environment could modulate fetal programming by an increase in microglia and astrocytes miRNA155. This scenario may lead to the more severe EAE observed in pups exposed to ETS in utero.